"You Are not Under the Law but Under Grace:" A Study of Romans 6:14 - Axworthy Daryl Samuel Terrence (Jurnal Koinonia, 2022)
Romans 6:14 mentioned of the moral law and grace of God and is one of misunderstood texts. This research uses the methodology of theological study and analysis to elucidate the correct meaning of Romans 6:14. Paul understood that humans are no longer under the condemnation of the law, but under gracious dispensation and still under the jurisdiction of the law. Under grace means that men are justified by faith and redeemed from the curse of law through Christ. Christians living under the dispensation of grace are enabled to have victory over the dominion of sin as the Holy Spirit guided the life because law has now been written in the hearts of believers. The Ten Commandments does not provide salvation or remove sin, but it can lead the sinners to seek a remedy for guilt, to point out sins and at the same time point to Jesus.